Teaching Morality with Acehnese Idioms in Indonesia - Yusri Yusuf; Jarjani Usman; Wildan Wildan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Every society has its local pearls of wisdom in educating its generations. In the western part of Indonesia, Acehnese society frequently uses figurative language, like idioms, as a tool for teaching morality to their generations. Even though research on local society's use of local wisdom to educate their generations has existed, research on the use of idioms in the Acehnese language is scant. This study investigated whether idioms in the Acehnese language contain educational values. In doing so, this study used interviews to collect data and involved 14 respondents from seven districts in Aceh that use a similar dialect of the Acehnese language, including Aceh Utara, Aceh Timur, Lhokseumawe, Bireuen, Aceh Besar, Pidie, and Banda Aceh. The results showed ten hand-related idiomatic expressions in the Acehnese language fall into pure idioms and semi-literal idioms. The idioms are used to teach moral values, such as encouragement to work, hardworking, responsibility, diligence, creativity, and many more. In conclusion, there is a nexus between the Acehnese hand-related idioms in the Acehnese society in Indonesia and the educational values they embrace.